Pengaruh inkuiri berbasis pictorial riddle berbantuan phet simulation untuk meningkatkan hasil belajar peserta didik kelas X SMAN 13 Padang pada materi momentum, impuls dan getaran harmonis sederhana - arifaldi arifaldi; Ramli Ramli; Yenni Darvina; Silvi Yulia Sari (PILLAR OF PHYSICS EDUCATION, 2019)
In learning the teacher still uses conventional models and methods so that students do not play an active role. This has a negative impact on student learning outcomes and has not achieved the objectives of the 2013 curriculum which requires students to play an active role in learning. Simple pictorial-based inquiry learning is expected to be able to train students to observe, ask, try, associate and communicate, with that the increase in the results of these students will increase. This type of research is pre-experimental designs. The form of the research design that will be used is the One Group Pretest-Posttest Design. The population in this study were students of class X MIPA 6 of SMAN 13 Padang who were enrolled in the 2018/2019 Academic Year totaling 33 people. Sampling in this study using Cluster Random Sampling technique. The data in this study were analyzed using descriptive analysis, normality test, homogeneity test and hypothesis testing to determine the influence of independent variables on aspects of knowledge competence. Based on data analysis that has been done in the experimental class, two research results can be presented. The results showed that the average value of knowledge in the post-test was 78.6 higher than the pre-test of 31.1. The results of the hypothesis obtained the results of the study have t count  > t table. with differences in the ability of students that were significant at a significant level of 0.05. This shows the use of pictorial riddle-based inquiry models assisted by phet simulation on simple material of momentum, impulses and harmonious vibrations on learning outcomes of class X students of SMAN 13 Padang. Able to make a greater contribution to improving student learning outcomes